Introduction to Solid State Physics and Crystalline Nanostructures - Iadonisi, Giuseppe; Cantele, Giovanni; Chiofalo, Maria Luisa; SpringerLink (Online service) (Milano : Springer Milan : Imprint: Springer, 2014)
This textbook provides conceptual, procedural, and factual knowledge on solid state and nanostructure physics. It is designed to acquaint readers with key concepts and their connections, to stimulate intuition and curiosity, and to enable the acquisition of competences in general strategies and specific procedures for problem solving and their use in specific applications. To these ends, a multidisciplinary approach is adopted, integrating physics, chemistry, and engineering and reflecting how these disciplines are converging towards common tools and languages in the field. Each chapter discusses essential ideas before the introduction of formalisms and the stepwise addition of complications. Questions on everyday manifestations of the concepts are included, with reasoned linking of ideas from different chapters and sections and further detail in the appendices. The final section of each chapter describes experimental methods and strategies that can be used to probe the phenomena under discussion. Solid state and nanostructure physics is constantly growing as a field of study where the fascinating quantum world emerges and otherwise imaginary things can become real, engineered with increasing creativity and control: from tinier and faster technologies realizing quantum information concepts, to understanding of the fundamental laws of Physics. Elements of Solid State Physics and of Crystalline Nanostructures will offer the reader an enjoyable insight into the complex concepts of solid state physics.
Crystals and Nanosystems Structure -- Electronic structure of nanosystems and crystals -- Elements of continuum mechanics and lattice vibrations -- Transport and Equilibrium Properties -- Optical Properties -- Correlations and Density Functional Theory.
Keywords: Physics; Nanochemistry; Solid state physics; Crystallography; Mechanical engineering; Nanotechnology; Physics; Physics, general; Solid State Physics; Nanotechnology; Mechanical Engineering; Nanochemistry; Crystallography; Electronic books